Psychology Impact of Design-Based Students during Covid-19 Pandemic in Malaysia - Rostam Yaman; Fatin Aziz; Farrah Zuhaira Ismail; Noraini Ahmad; Muhammad Fuad Abdullah; Mohamad Pirdaus Yusoh; Faezah Pardi; SitiAekbal Salleh (Journal for ReAttach Therapy and Developmental Diversities, 2023)
COVID-19 Pandemic has created a new-norm society throughout the world. This is also impacting the architectural education conduct of university students. The aim of this study is to assess psychological impact of design-based students during Covid-19 pandemic. The objective of the study is to measure 18 psychological impact factor level of UiTM students' using five points Likert scale during the pandemic. The major findings indicate varies factors hierarchical level of impacts on design-based students and remedial actions should be taken to minimize the impacts.